Outcome of long-term treatment with the 5α-reductase inhibitor finasteride in idiopathic hirsutism: clinical and hormonal effects during a 1-year course of therapy and 1-year follow-up - Castello, Roberto; Tosi, Flavia; Perrone, Fabrizia; Negri, Carlo; Muggeo, Michele; Moghetti, Paolo (Fertility and sterility, 1996)
To evaluate the long-term efficacy of the 5α-reductase inhibitor finasteride in idiopathic hirsutism. Prospective clinical study. Outpatients in a university hospital. Fourteen young women with idiopathic hirsutism. Finasteride, 5mg once daily, was given for 12 months. Degree of hirsutism, graded by a modified Ferriman and Gallwey score, serum sex hormones, and serum and urinary markers of 5α-reductase activity. Clinical outcome was evaluated up to and including the 1-year post-treatment period. The Ferriman and Gallwey score showed a remarkable reduction after 12 months of finasteride treatment (4.4 ± 0.7 versus 11.8 ± 1.0; mean ± SEM). Serum levels of the two 5α-reductase activity markers, dihydrotestosterone and 3α-androstanediol glucuronide, decreased, and urinary C19 and C21 5β:5α steroid metabolite ratios consistently increased during finasteride administration. These changes were reversed readily after cessation of treatment. No significant adverse effect was reported. Nine of 14 women completed the 1-year post-treatment follow-up. Their hirsutism scores were increased substantially as compared with values recorded at the end of therapy, but still were lower than baseline values. The 5α-reductase inhibitor finasteride is effective and well tolerated in long-term treatment of women with idiopathic hirsutism. Post-treatment follow-up suggests that drug effects on hair growth are sustained in the majority of subjects with this disorder.